Pengaruh Intensitas Menonton Drama Korea Terhadap Prokrastinasi Salat Fardu - Nur Badriah (UIN Sunan Gunung Djati Bandung, 2022)
The aims of this study are: 1) Knowing the level of intensity of watching Korean dramas by students 2) Knowing the level of procrastination of fardu prayers in students 3) Knowing the effect of the intensity of Korean dramas on procrastination of fardu prayers in students. This study uses a quantitative approach with a descriptive method. While the data collection techniques are observation, interviews and questionnaires. The data analysis uses a statistical approach, namely partial analysis, normality test and correlation test. The results showed that the correlation between variables X and Y variables was negative from the coefficient value of -0.24. So that there is no level of influence of the intensity variable watching Korean dramas on procrastination of fardu prayers in students. This means that students still have full awareness to continue to carry out their obligations, namely fardu prayers according to a predetermined time or not to delay.